Assets Misappropriation in the Malaysian Public and Private Sectors - K. Norziaton, I.; D.Mohamad Ridhuan, M.; N. Nur Adura, A. (International Journal of Engineering and Technology, 2018)
Assets misappropriation is becoming a major concern in organizations. Over the years, the Malaysian Auditor General has reported high occurrences of assets misappropriation at the federal, state and even local governments. It is surprising that not only assets misappropriation is a major concern in the public sector but also has indicated that it is a common sight in all organizations. The current trend is rather disconcerting because employees are accountable to perform their jobs at the interest of the organizations. Various researches in the past found that the incidence of assets misappropriation occurs when employees used the official vehicles, internet connection, computers, stationery and facilities for personal and family benefits. The issue of assets misappropriation has been increasing and is the highest among other types of frauds. Even though the issue seems to be trivial, yet, if it is left untreated, the symptom will become an incurable disease that it will cause major leakages to the organizations. Hence, this paper highlights the common practices and issues of assets misappropriation in public and private organizations. It also discusses why the acts of assets misappropriation occur. The paper concludes that to promote awareness of the public and private sectors employees is vital in the issues of assets misappropriation.Â Â Â